SERGE RAYNAUD DE LA FERRIÈRE’S DOCTRINE READJUSTMENT: THE UGB AND THEOCRACY (Религиски дијалог и соработка, 2025)
Serge Raynaud de la Ferrière (1916-1962) left his native France to the Americas. He knewthe predominance of America for the New Age of Aquarius that was about to begin. In 1948 hefounded the Great Universal Brotherhood (UGB) in Caracas, Venezuela, a worldwide and culturalinstitution to re-educate humanity. After traveling the five continents, he returned to Europe in1953. Right after he re-established communication with his disciples in America, he noted that hiswork and literature was being deformed. He even said that he couldn’t recognize his own foundation!Consequently, he began readjusting his work and wrote most part of his extensive literature.In this period, Ferriz, his fourth and last emblematic disciple appeared. He translated under hissupervision some of his most important texts, and among other tasks he asked him to write hisbooks’ prologue, exegesis and be his Literature’s Coordinator. In the context of the New Age, R. dela Ferrière discusses theocracy and mentioned some precursor signs for its advent. These are brieflydiscussed in this essay. They were misinterpreted by his other emblematic disciples – contrary to hisidea of a government of wise people. They believed in absolute authority and autocratic governmentthat in various instances they applied it in the UGB. Ferriz asserts that this was probably theseed that caused their failure to follow R. de la Ferrière’s Readjustment and created an ideologicaland doctrinaire difference between their beliefs and R. de la Ferrière’s thought. In 1990, to safeguardthe original UGB and R. de la Ferrière’s thought, Ferriz left in Exodus the deformed UGB andcreated a new one.